(untitled) (Interfaces - Revista de Extensão da UFMG, 2016)
The school is an appropriate environment for the development of actions in health and education to promote the prevention of bone metabolic diseases. Students of the University of Sao Paulo (USP) organized lectures and informative activities about this issue for high school students aiming to encourage preventive postures. At the end of these classes a positive reception and approval in relation to these activities were done by the students and teachers. These people participated through the recitation asking and answering questions about different experiences through dialogue. Thus, the involvement in the Culture and Extension program provide a narrowing between the academic community and the public. This project helps to structure disseminative informative agents and aware about the reality and current problems, aiming positive attitudes related to prevention of future problems that may affect the quality of life.